Inhibitition on H22 Allografts, HepG2 and SMMC-7721 Human Hepatoma Cells of Adlay Seed Extracts - Gong, Xiao-Jie; Bao, Yong-Rui; Diao, Yun-Peng; Teng, Jian-Ye; Meng, Xian-Sheng; Kang, Ting-Guo (Asian Journal of Chemistry, 2011)
To examine the effects of effective chemical substances of adlay seed on the hepatoma in vitro and in vivo. H22 cancer-bearing mice were chosen to observe the effects of tumor inhibiting effective chemical substances of adlay seed, drug-containing serum were prepared by serum pharmacology method. MTT assay was used to observe the proliferation inhibition rate of HepG2 and SMMC-7721 cells after incubation with the drugs containing serum. The effective chemical substances of adlay seed could inhibit the growth of H22 cancer in mice, the tumor inhibition rate of the different concentration was 42.46, 38.05, 33.31 % and the drug-containing serum could obviously inhibit the growth of HepG2 and SMMC-7721 cells.The effective chemical substances of adlay seed has the effect on inhibiting the growth of hepatoma.